Keluarga Berencana dalam Perspektif Islam dan Kesehatan: Harmonisasi antara Syariat dan Medis Modern - Nabilah Falah (Sahaja: Journal Sharia and Humanities, 2025)
This study examines the harmonization between Islamic legal principles and modern medical science in the implementation of family planning (FP) programs in Indonesia. Despite the government's sustained efforts to promote FP through the National Population and Family Planning Board (BKKBN), religious misinterpretations and cultural resistance continue to impede program acceptance, particularly in Muslim-majority communities. Employing a qualitative normative-analytical approach through systematic literature review, this research analyzes primary Islamic legal sources, national health policies, and recent empirical studies indexed in Scopus and Web of Science databases (2020-2025). The analysis is framed through the theoretical lens of maqasid al-shari'ah, specifically the principles of hifz al-nafs (preservation of life) and hifz al-nasl (preservation of lineage). The findings reveal that temporary contraception is jurisprudentially permissible when aimed at safeguarding maternal and child health, and that the integration of religious authority and biomedical evidence significantly enhances community acceptance. This study contributes to the interdisciplinary discourse on Islamic bioethics by proposing a conceptual model for religion-health integration in reproductive governance